1985
DOI: 10.1136/bmj.291.6505.1330
|View full text |Cite
|
Sign up to set email alerts
|

What happens to defaulters from a diabetic clinic?

Abstract: The annual rate at which patients defaulted from follow up at the Wolverhampton diabetic clinic between 1971 and 1981 was 4-1% overall and 3 5% in white patients. In 1982 a study was started to discover what happened to white patients, born after 1919, who defaulted from the hospital clinic. There were 162 defaulters, of whom 19 had died. Of the remaining 143 patients, 19 were attending another hospital diabetic clinic, 22 had moved out of the area, and 28 refused to participate in the study. Seventy four agre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
75
1

Year Published

1989
1989
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 8 publications
2
75
1
Order By: Relevance
“…The data conflict with those from specialist clinics and studies of type 1 diabetes care, which have suggested that nonattenders are more likely to suffer from complications (8,9) and are more likely to smoke (9). The data do confirm the findings of Graber et al (9), who showed that nonattenders are less likely to have been prescribed medication.…”
Section: Results -contrasting
confidence: 52%
“…The data conflict with those from specialist clinics and studies of type 1 diabetes care, which have suggested that nonattenders are more likely to suffer from complications (8,9) and are more likely to smoke (9). The data do confirm the findings of Graber et al (9), who showed that nonattenders are less likely to have been prescribed medication.…”
Section: Results -contrasting
confidence: 52%
“…The reasons for dropout from a diabetic care can be generally summarized into the following three categories: 1) patient-oriented problem (2,(11)(12)(13)(14)(15)(16)(17), 2) health-care provideroriented problem (11,18,19), and 3) physician-patient relationship (5,20). For the patient-oriented problem, gender, age, ethnicity, educational level, economical status, tobacco use, obesity, the duration of disorder, glycemic control, and psychological problems among others can be considered.…”
Section: Introductionmentioning
confidence: 99%
“…Clinic-based estimates of the regional prevalence of complications will be biased if clinic-attenders have more or fewer complications than the population of IDDM patients from which the attenders are drawn. While some patients may be referred to clinics because of advanced complications, others' motivation to attend may be associated with better control and fewer complications than in non-attenders [10]. Individual clinics may therefore over-or underestimate the regional prevalence of complications, depending on the balance between these opposing biases.…”
Section: Discussionmentioning
confidence: 99%